Distribution and seasonality of horseflies (Diptera: Tabanidae) in Van province of Türkiye with new records - Ferhat Altunsoy; Bahriye Ayaz (Journal of Insect Biodiversity and Systematics, 2024)
This study was conducted in Van province, which is located in the eastern region of Türkiye. The study area is located in the Irano-Anatolian hotspot region, divided to the east and west by the Anatolian diagonal. Here, we demonstrate the diversity, distribution, and seasonality of horseflies. Malaise and water traps were used to collect adult horseflies. A total of 1026 specimens were collected and 52 species identified. Chrysops divaricatus Loew, 1858; Haematopota csikii Szilady, 1922; Haematopota pallidula (Krober, 1922) and Haematopota turkestanica (Krober, 1922) were recorded for the first time from Türkiye. The distribution and seasonality of the species were presented.